2011
DOI: 10.1007/s10162-011-0273-4
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inner Hair Cell Loss in Prematurity: A Temporal Bone Study of Infants from a Neonatal Intensive Care Unit

Abstract: Premature birth is a well-known risk factor for sensorineural hearing loss in general and auditory neuropathy in particular. However, relatively little is known about the underlying causes, in part because there are so few relevant histopathological studies. Here, we report on the analysis of hair cell loss patterns in 54 temporal bones from premature infants and a control group of 46 bones from full-term infants, all of whom spent time in the neonatal intensive care unit at the Hospital de Niños in San Jose, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 32 publications
(29 reference statements)
1
30
1
1
Order By: Relevance
“…This is similar to the research conducted by Pourarian et al and Santoso, that sepsis is not a risk factor for cochlear dysfunction. [15,16] However, these results differ from previous studies conducted by Meyer et al revealed that infants with a history of sepsis have a risk of 2.57 (95% CI 1.12 to 5.91) underwent cochlear dysfunction. [8] The un significant sepsis as risk factors cochlear dysfunction may be caused by the development of early detection of sepsis and the development of antibiotics in the treatment of sepsis in infants so that better management of sepsis and further complications can be prevented.…”
Section: Discussioncontrasting
confidence: 56%
“…This is similar to the research conducted by Pourarian et al and Santoso, that sepsis is not a risk factor for cochlear dysfunction. [15,16] However, these results differ from previous studies conducted by Meyer et al revealed that infants with a history of sepsis have a risk of 2.57 (95% CI 1.12 to 5.91) underwent cochlear dysfunction. [8] The un significant sepsis as risk factors cochlear dysfunction may be caused by the development of early detection of sepsis and the development of antibiotics in the treatment of sepsis in infants so that better management of sepsis and further complications can be prevented.…”
Section: Discussioncontrasting
confidence: 56%
“…Pathological insults to different cochlea locations and auditory neurons are not uniform in patients with ANSD and patients with SNHL (e.g. Amatuzzi et al, 2011; He et al, 2012; Makary et al, 2011), which might account for, at least partially, the variations in group effects on these dependent variables at different electrodes. No difference in averaged N1 latency was observed between children with ANSD and children with SNHL.…”
Section: Discussionmentioning
confidence: 99%
“…For example a high incidence of auditory neuropathy is found in infants born prematurely (Xoinis et al, 2007). Recently, a study of infant temporal bones revealed that 30% of preterm babies who died in the NICU had selective inner hair cell (IHC) loss, while only 3% of full-term infants presented such a phenotype (Amatuzzi et al, 2011). This high prevalence for such a rare histopathology (Schuknecht, 1993) suggested that selective IHC loss might be a common cause of auditory neuropathy.…”
Section: Introductionmentioning
confidence: 99%